Introduction to piezoelectricity and electrospun piezoelectric materials and devices - Rodrigues-Marinho, T. (2020)
Piezoelectric materials are increasingly being used in a wide range of applications. Single crystals, ceramics and polymers are all being used sensors, actuators and energyharvesting applications. Among the most used piezoelectric materials are lead zirconate titanate (PZT) and barium titanate (BaTiO3) ceramics and the polymer poly(vinylidene fluoride) (PVDF). Polymer-based composites including high dielectric and piezoelectric ceramic nano- or microparticles are also largely investigated to take advantage of the advantageous properties of both polymers and ceramics. Among the different processing methods, electrospinning allows the development of piezoelectric nano- and microfibers opening a distinct range of applications in electronics, energy generation and storage or membranes for water and air remediation.